CornCob And Sugar Cane Waste as a Viscosivier in Drilling Fluid - Sonny Irawan, Sonny; Ismail B. Saaid, Ismail (Uiversiti Putera Malaysia, 2009)
The present project investigates the potential of utilizing corncob and sugar cane waste as viscosifier for hydrocarbon drilling fluid. A synthetic-based drilling fluid, Sarapar 147, has been used as the base fluid. Both materials were subjected to pre-treatment of drying, dehumidifying, grinding and sieving process prior to rheological tests. Rheological tests were conducted in accordance to API 13B specifications to measure mud density, plastic viscosity, yield point, 10-second and 10-minute gel strengths. The study found that the plastic viscosity and yield point had a direct relationship with the amount of materials added. For drilling fluid additive with corncob and sugar cane waste, as the amount of additives is increased, the density, plastic viscosity and yield point increase as well. Based on experiments, both additives have the potential to be used as viscosifier in hydrocarbon drilling fluid. They were able to improve its rheological properties by increasing the density, plastic viscosity and yield point. The suitable dose for corncob and sugar cane waste is 6.45 lb/bbl and 9.43 lb/bbl respectively.